2022
DOI: 10.1371/journal.pone.0269201
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of online college science courses that alleviate and exacerbate undergraduate depression

Abstract: Depression is a top mental health concern among college students, yet there is a lack of research exploring how online college science courses can exacerbate or alleviate their depression. We surveyed 2,175 undergraduates at a large research-intensive institution about the severity of their depression in large-enrollment online science courses. The survey also explored aspects of online science courses that exacerbate or alleviate depression and we used regression analyses to assess whether demographics predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Therefore, instructors, schools, and governments should take notice of the current situation and figure out ways to collaboratively help online learning students relieve anxiety, depression, and stress against the backdrop of the COVID-19 pandemic. Instructors, as the group with the closest connections to students, could alleviate students’ negative emotions by designing flexible coursework and test-taking, having organized online courses, and showing care about students’ mental health ( Mohammed et al, 2021 ; Busch et al, 2022 ). From the schools’ perspective, professional programs for reducing students’ mental disorders, such as anxiety, depression, and stress, could be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, instructors, schools, and governments should take notice of the current situation and figure out ways to collaboratively help online learning students relieve anxiety, depression, and stress against the backdrop of the COVID-19 pandemic. Instructors, as the group with the closest connections to students, could alleviate students’ negative emotions by designing flexible coursework and test-taking, having organized online courses, and showing care about students’ mental health ( Mohammed et al, 2021 ; Busch et al, 2022 ). From the schools’ perspective, professional programs for reducing students’ mental disorders, such as anxiety, depression, and stress, could be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of students in online courses found that students perceived being cared for by instructors who made clear acknowledgments about mental health and provided resources on mental health in course materials [15]. Additionally, students in this same study reported an exacerbation of depression when courses did not provide both formal and informal interaction time between students and the professor, due to increased feelings of isolation [15]. More research should be done to investigate ways to increase caring and connectedness in online environments.…”
Section: Discussionmentioning
confidence: 76%
“…Of concern from the MUSIC model data, was that the Caring dimension of the MUSIC model revealed the lowest score for both semesters indicating a need to be more intentional in an online learning environment to make students feel cared for. A recent study of students in online courses found that students perceived being cared for by instructors who made clear acknowledgments about mental health and provided resources on mental health in course materials [15]. Additionally, students in this same study reported an exacerbation of depression when courses did not provide both formal and informal interaction time between students and the professor, due to increased feelings of isolation [15].…”
Section: Discussionmentioning
confidence: 82%
“…, 2022 ). The proportion of undergraduates in the sciences who struggle with depression is likely even higher, with a recent study finding that more than 50% of science majors identify as having depression ( Busch et al. , 2022 ).…”
Section: Introductionmentioning
confidence: 99%